Effect of COVID-19 on maintaining balance in highly skilled handball players - Fernández-Rodríguez, E.; Niznikowski, T.; Ramos, O. R.; Markwell, L. (Polish Journal of Sport and Tourism, 2023)
Introduction. The aim of this study was to evaluate the effect of COVID-19 on maintaining balance in highly skilled handball players during the performance of the modified Romberg test.